Isolation and characterization of sulfur compounds in a lacustrine crude oil. (1st October 2019) - Wu, Jianxun; Zhang, Weilai; Ma, Chao; Wang, Feilong; Zhou, Xuan; Chung, Keng H.; Hou, Dujie; Zhang, Yahe; Shi, Quan
Abstract: A high-sulfur (4.69 wt%) crude oil was discovered in the China Bohai Bay Basin which is known to contain low sulfur crude oil. The composition of this high sulfur crude oil and its geological origin are unknown. In this study, thiophenic and sulfidic sulfur compounds were isolated from the crude oil by methylation/demethylation and characterized using Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) and gas chromatography-mass spectrometry (GC–MS). Relatively high abundance of sulfur compounds with 30 carbon atoms and 5–7 double bond equivalence (DBE), which were assigned to sulfurated steranes with thiophene or tetrahydrothiophene moieties. Some of these compounds have not been reported in fossil fuels. In addition to commonly found sulfur compounds in petroleum feedstock, such as benzothiophenes and dibenzothiophenes, other structural sulfur compound types were detected: long-chain 2, 5-di- n -alkylthiolanes, 2, 5-di- n -alkylthianes, bicyclic terpenoid sulfides, isoprenoid thiophenes, and isoprenoid benzothiophenes. The presence of abundant biomarker sulfur compounds suggests that the sulfuration of the high sulfur crude oil was occurred in the early diagenesis stage instead of a thermochemical sulphate reduction (TSR) process.